2009
DOI: 10.1111/j.1471-4159.2009.05951.x
|View full text |Cite
|
Sign up to set email alerts
|

Densin‐180: revised membrane topology, domain structure and phosphorylation status

Abstract: Densin‐180 is a core component of post‐synaptic densities, the highly complex molecular assemblies that mediate signaling between neuronal cells. It is a multi‐domain scaffold protein characterized by multiple leucine‐rich repeat domains plus a single Psd95/Discs large/Zona occludens‐1 domain. In its original topology model a single transmembrane segment was proposed with an extracellular N‐terminus and an intracellular C‐terminus. However, recently discovered in vivo phosphorylation sites are incompatible wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…All sites mentioned above have also been identified in PNGaseF-treated samples (53). The site-specific location of newly detected PTMs is a valuable tool to provide support for models of transmembrane topology, and on rare occasion will trigger a re-evaluation of the prevalent model for an individual protein (66).…”
Section: Fig 4 Etd Spectrum Of 3100 Ngat(galglcnacfuc)c(carbamidomementioning
confidence: 92%
“…All sites mentioned above have also been identified in PNGaseF-treated samples (53). The site-specific location of newly detected PTMs is a valuable tool to provide support for models of transmembrane topology, and on rare occasion will trigger a re-evaluation of the prevalent model for an individual protein (66).…”
Section: Fig 4 Etd Spectrum Of 3100 Ngat(galglcnacfuc)c(carbamidomementioning
confidence: 92%
“…While O-GlcNAcylation occurs almost exclusively on intracellular protein regions, the extracelluar domain of Notch is O-GlcNAcylated (26). Peptides were assigned as ambiguous between O-GalNAcylated or O-GlcNAcylated based upon their annotation in UniProt (downloaded April 2011) as located in extracelluar or luminal regions, without further corrections (27). In the case of transmembrane proteins, UniProt topological information was used when available to determine protein extracellular and cytosolic regions.…”
Section: Methodsmentioning
confidence: 99%
“…Biochemical analyses have revealed that the PSD-enriched samples consist of hundreds of proteins (19 -26). More recently, the abundance of several components in the PSD have been quantified by a variety of techniques (27)(28)(29)(30), and the phosphorylation and glycosylation states of PSD proteins have further been studied (31)(32)(33)(34).…”
Section: Postsynaptic Density (Psd)mentioning
confidence: 99%